A Systematic Review on Teacher Training in Educational Robotics: Global and Brazilian Perspectives - Santos, Lídia Gabrielly Dutra de Meneses; Curvelo, Carla da Costa Fernandes; Gonçalves, Luiz Marcos Garcia (Anais do Simpósio Brasileiro de Robótica e Simpósio Latino Americano de Robótica (SBR/LARS), 2025)
This paper presents a systematic literature review on teacher training in educational robotics, with a twofold objective: to map the global research landscape and to provide a focused analysis of the Brazilian context. The review was guided by spe-cific research questions and conducted using the Scopus and Web of Science databases for the global perspective, complemented by the Brazilian Digital Library of Theses and Dissertations (BDTD) for the local analysis. Our findings highlight Brazil's significant international contribution, ranking second in the number of publications in both Scopus (6 out of 28) and Web of Science (4 out of 15). At the national level, our analysis identified 11 recent theses and dissertations completed between 2020 and the present. These results indicate that robust methodologies for teacher training in Educational Robotics are not only being actively researched but also effectively implemented throughout Brazil.